Hybrid Trust Management in Cloud Computing - D. Ramya Swathi, Dr. V. Srikanth (International Journal of Advanced Science and Technology, 2020)
Cloud Trust is an important aspect in cloud computing services and cloud need to manage different cloud activities and user data to ensure the data security. The relationship of trust between cloud service providers and their customers should be preserved by a trust management system, which in effect would have a direct impact on the quality of their engagement. But at the other side, in the field of trust management the detection of malicious feedbacks remains a significant task. Cloud computing trust management is divided into different groups, namely Reputation Based Trust technique, SLA-based trust assurance, Government-based trust, organizational trust, suggestion-based trust management technique and confidence-based prediction technique. In this system we created the hybrid trust model to determine the trust efficiency by validating the various trust schemes and employed the cryptography model to analyse the time taken process.